The Role of Anti-NHba Antibody in Bactericidal Activity Elicited by the Meningococcal Serogroup B Vaccine, MenB-4C - Partridge, Elizabeth (Vaccine, 2017)
BACKGROUND: MenB-4C (Bexsero®) is a multicomponent serogroup B meningococcal vaccine. For vaccine licensure, efficacy was inferred from serum bactericidal antibody (SBA) against three antigen-specific indicator strains. The bactericidal role of antibody to the fourth vaccine antigen, Neisserial Heparin binding antigen (NHba), is incompletely understood. METHODS: We identified nine adults immunized with two or three doses of MenB-4C who had sufficient volumes of sera and >3-fold increases in SBA titer against a strain with high NHba expression, which was mismatched with the other three MenB-4C antigens that elicit SBA. Using 1 month-post-immunization sera we measured the effect of depletion of anti-NHba and/or anti-Factor H binding protein (FHbp) antibodies on SBA. RESULTS: Against three strains matched with the vaccine only for NHba, depletion of anti-NHba decreased SBA titers by an average of 43–79% compared to mock-adsorbed sera (P<0.05). Despite expression of sub-family A FHbp (mismatched with the subfamily B vaccine antigen), depletion of anti-FHbp antibodies also decreased SBA by 45–64% (P<0.05). Depletion of both antibodies decreased SBA by 84–100%. Against a strain with sub-family B FHbp and expression of NHba with 100% identity to the vaccine antigen, depletion of anti-NHba decreased SBA by an average of 26%, compared to mock-adsorbed sera (P<0.0001), and depletion of anti-FHbp antibody decreased SBA by 92% (P<0.0001). CONCLUSIONS: Anti-NHba antibody can contribute to SBA elicited by MenB-4C, particularly in concert with anti-FHbp antibody. However, some high NHba-expressing strains are resistant, even with an exact match between the amino acid sequence of the vaccine and strain antigens.